Search for non-relativistic magnetic monopoles with IceCube - Aartsen, MG; Abbasi, R; Ackermann, M; Adams, J; Aguilar, JA; Ahlers, M; Altmann, D; Arguelles, C; Arlen, TC; Auffenberg, J; Bai, X; Baker, M; et al. (SpringerOpen, 2014)
In the analyses, published in Ref. [1], the exclusion limits are calculated in dependence of the mean free path of the magnetic monopole - nucleon catalysis interaction.